Pembuatan Video Animasi 2D “Kandungan Bahan Berbahaya Dalam Produk Skincare” Berbasis Motion Graphic - Maya Hasifa; Anton Topadang (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
The rapid growth of the cosmetics industry has led to the hazardous skincare products (containing mercury, hydroquinone, etc.). As a solution, this study created an educational 2D motion graphic animation video using the MDLC method (from concept to distribution). The video, uploaded to the POLNES YouTube channel, has garnered over 6,000 views. Based on a survey of 125 respondents, the video received an average rating of 90%, demonstrating that its information delivery is engaging, easy to understand, and effective in raising public awareness about choosing safe skincare products.